Gender Gaps in the Effects of Childhood Family Environment: Do They Persist into Adulthood? - Anne Ardila Brenøe; Shelly Lundberg (Institute for the Study of Labor (IZA), 2016)
We examine the differential effects of family disadvantage on the education and adult labor market outcomes of men and women using high-quality administrative data on the entire population of Denmark born between 1966 and 1995. We link parental education and family structure during childhood to male-female and brother-sister differences in teenage outcomes, educational attainment, and adult earnings and employment. Our results are consistent with U.S. findings that boys benefit more from an advantageous family environment than do girls in terms of the behavior and grade-school outcomes. Father's education, which has not been examined in previous studies, is particularly important for sons. However, we find a very different pattern of parental influence on adult outcomes. The gender gaps in educational attainment, employment, and earnings are increasing in maternal education, benefiting daughters. Paternal education decreases the gender gaps in educational attainment (favoring sons) and labor market outcomes (favoring daughters). We conclude that differences in the behavior of school-aged boys and girls are a poor proxy for differences in skills that drive longer-term outcomes.
Keywords: I20; J1; J2; J3; 330; education; family structure; parental education; gender gap; labor market outcomes